Селекція нових ліній ячменю waxy - Козаченко, М.Р.; Наумов, О.Г.; Васько, Н.І.; Солонечний, П.М.; Солонечна, О.В.; Важеніна, О.Є.; Садовой, О.О. (Фактори експериментальної еволюції організмів, 2016)
Aim. The aim of this research was to create waxy barley forms by hybridization and to test them for high amylopectin content in starch. Methods. To create high-yielding waxy lines, we used hybridization methods. Results. Due to using spring barley forms with various amylopectin content in starch in breeding, high-yielding lines with starch, which almost completely consists of amylopectin, were effectively created. The range of lines with amylopectin starch was broadened: nutans, medicum and rikotense were obtained. In 2014–2015, the variety trials distinguished the best eight lines, seven of which (12-945, 12-954, 12-965, 12-1014, 12-333, 12-473, 12-476) gave high yields (107%, 105%, 105%, 116%, 110%, 107%, 115% related to the standard) and were lodging resistant (8.5–9.0 points) with identical or slightly different duration of the vegetation period. The waxy lines distinguished are sources of high amylopectin content in starch and valuable agricultural characteristics. Conclusions. The effectiveness of high-yielding waxy line breeding was shown. Waxy lines with 5–16% higher yield capacity and high lodging resistance (8.5–9.0 points) were selected. Keywords: spring barley, waxy starting form, waxy line, amylopectin, yield.